Bone Maturation as a Predictive Factor of Catch-Up Growth During the First Year of Life in Born Small for Gestational Age Infants: A Prospective Study - Pepe, Giorgia; Calafiore, Mariarosa; Valenzise, Mariella; Corica, Domenico; Morabito, Letteria; Pajno, Giovanni Battista; Aversa, Tommaso; Wasniewska, Malgorzata (Frontiers in Endocrinology, 2020)
BACKGROUND: About 85-90% of children born small for gestational age (SGA) experience a catch-up growth that occurs mostly during the first year of life and results in a full stature recovery by the age of 2. OBJECTIVE: to investigate the relation between bone maturation (BM) and catch-up growth during the first year of life in SGA infants. METHOD: Newborns whose weight and/or length was <-2 SD for gestational age were classified as SGA (group A). The study included a group of 32 SGA, 21 of which full-term (37-41 gestation weeks GW, subgroup A1) and 11 preterm (30-36 GW, subgroup A2). Control group (B) consisted of 19 full-term and adequate for gestational age (AGA) newborns. All the partecipants were born in the same hospital and period (January-December 2017). Chromosomal disorders, congenital defects and maternal chronic diseases were criteria of exclusion. The study population underwent longitudinal evaluation of growth parameters and BM at 0, 3, 6 and 12 months. Assessment of BM was performed by ultrasonographyc (US) study of Beclard’s nucleus (<3 mm at birth meaning intrauterine delay of BM). RESULTS: Significantly higher height velocity (HV) was observed in subgroup A2 versus A1 (32.4±8.0 vs 25.6±2.9 cm, p=0.01); nevertheless, more subjects in subgroup A2 had height <-2 SD at year 1 compared to subgroup A1 (27.3% vs 0%, p=0.01). Intrauterine delay of BM was more common in group A vs B (59.4% vs 21.2%, p=0.0078), and in subgroup A2 vs A1 (90.9% vs 42.9%, p=0.0086). In group A, HV over the first year of life negatively correlates with NB diameter assessed at birth (r=-0.6, p<0.001), but positively correlates with NB growth (r=0.52, p<0.01). Moreover, SGA babies with intrauterine delay of BM showed higher HV and better height gain at 12 months evaluation, compared to SGA with adequate BM (29.75±3.1 vs 23.8±2.7 cm, p=0.003). CONCLUSION: neonatal BM should be regarded as a predictive factor of SGA height gain during the first year of life. US evaluation of Beclard’s nucleus is a useful non–invasive technique to identify intrauterine delay of BM, which positively correlates with early postnatal catch-up growth of SGA infants.